Sleep and media use among children with neurodevelopmental disorders during the COVID-19 pandemic. Issue 4 (2nd October 2022) - Wilaisakditipakorn, Tanaporn Jasmine; Ievers-Landis, Carolyn E.; Malay, Sindhoosha; Burkhart, Kimberly; Ibrahim, Sally; Kralovic, Shanna; Diekroger, Elizabeth A.
ABSTRACT: Children with neurodevelopmental disorders commonly have sleep problems and higher screen time compared with their typically developing peers. Relationships of their media use to sleep are unknown during the COVID-19 pandemic. Seventy-five caregivers/parents of children ages 5–12 years with neurodevelopmental disorders completed surveys during the pandemic, reporting average child media use of 3.35 hours/day (SD = 0.36) and sleep duration of 9.22 hours (SD = 1.27). Media use duration was not significantly related to any sleep outcomes in the total sample. Unexpectedly, in subgroup analyses with COVID-19 exposure/distress variables, greater media use duration significantly related to less sleep-related impairment ( p = .012) and disturbance ( p = .0004). Clinical implications are that media use/sleep plans should be individually tailored for these at-risk children.